(untitled) - Krugman, Paul (Massachusett, 1996)
Krugman explains what real economic analysis is. He discusses economic terms and measurements, like "value-added" and GDP, in simple language so that readers can understand how pop internationalists distort, and sometimes contradict, the most basic truths about world trade
Keywords: International economic relations,Quan hệ kinh tế quốc tế,International trade,Thương mại quốc tế